MEKANISME CORPORATE GOVERNANCE DAN PENGUNGKAPAN ISLAMIC SOCIAL REPORTING PADA PERBANKAN SYARIAH DI INDONESIA DAN MALAYSIA - Nugraheni, Peni; Yuliani, Rahma Dwi (Ekonomi Syariah IAIN Kudus, 2017)
The high growth of the Islamic financial institution raises the qustion of the extent of their social responsibility towards the environment. Especially Islamic values attached to these institutions provide the demand to further contribute to the life of the community. This study aims at analyzing the influence of corporate governance mechanism toward Islamic Social Reporting (ISR) Disclosure in Islamic banking in Indonesia and Malaysia. These two countries have Muslim majority population and the high growth of Islamic financial institutions development. ISR disclosure is important to perform the accountability of Islamic bank to the accordance of Islamic principles and the environment. The paper uses corporate governance mechanism as factor to evaluate its influence toward ISR disclosure. The population in this study is all Islamic banks in Indonesia and Malaysia, which publish the annual report from 2012 to 2014. The research sample includes 33 data from 11 Islamic banks in Indonesia and 39 data from 13 Islamic banks in Malaysia. The technique that used in this study is panel regression with random effect model. Based on the analysis, the research finds that only the number of member and meeting of nomination and remuneration committee affecst positively toward ISR disclosure, while the dual position and number of meeting of sharia supervisory board, the institutional and foreign ownership do not have influence toward ISR disclosure.Perkembangan lembaga keuangan syariah memunculkan pertanyaan sejauh mana tanggung jawab social mereka terhadap lingkungan. Nilai-nilai Islam yang melekat padalembaga ini memberikan tuntutan sejauh mana kontribusi mereka pada masyarakat. Penelitian ini bertujuan untuk menganalisis pengaruh mekanisme corporate governance terhadap pengungkapan Islamic social reporting (ISR) dalam perbankan Islam di Indonesia dan Malaysia. Kedua negara ini memiliki penduduk mayoritas Muslim dan pertumbuhan lembaga keuangan Islam yang cukup pesat. Pengungkapan ISR merupakan hal yang penting untuk menilai akuntabilitas bank syariah terhadap kesesuaiannya dengan syariah dan terhadap lingkungan. Populasi dalam penelitian ini adalah bank umum syariah di Indonesia dan Malaysia yang memenuhi kriteria menerbitkan laporan tahunan dari 2012 hingga 2014. Sampel penelitian meliputi 33 data dari 11 bank syariah di Indonesia dan 39 data dari 13 bank syariah di Malaysia. Teknik analisis yang dipergunakan dalam penelitian ini ialah menggunakan regresi panel dengan efek acak. Berdasarkan hasil pengujian, penelitian ini menemukan bahwa hanya jumlah anggota dan jumlah rapat komite remunerasi dan nominasi yang berpengaruh positif terhadap pengungkapan ISR, sementara rangkap jabatan dan jumlah anggota DPS, kepemilikan institusional dan asing tidak berpengaruh terhadap pengungkapan ISR.